2001
DOI: 10.1590/s0100-879x2001000100005
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 subtypes among intravenous drug users from two neighboring cities in São Paulo State, Brazil

Abstract: In order to assess the molecular epidemiology of HIV-1 in two neighboring cities located near the epicenter of the HIV-1 epidemics in Brazil (Santos and São Paulo), we investigated 83 HIV-1 strains obtained from samples collected in 1995 from intravenous drug users. The V3 through V5 region of the envelope of gp 120 was analyzed by heteroduplex mobility analysis. Of the 95 samples, 12 (12.6%) were PCR negative (6 samples from each group); low DNA concentration was the reason for non-amplification in half of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
2
3

Year Published

2001
2001
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 7 publications
2
11
2
3
Order By: Relevance
“…The hypothesis of a higher prevalence of HIV-1 subtype F infections in IDUs vis-a-vis other populations has been discussed by researchers from São Paulo (Rossini et al, 2001;Sabino et al, 1996). However, although a high prevalence of HIV-1 subtype F has been verified among the IDU population from Rio de Janeiro, our studies did not confirm any specific segregation pattern in the IDUs so far assessed (Guimarães et al, 2001).…”
Section: Introductioncontrasting
confidence: 85%
“…The hypothesis of a higher prevalence of HIV-1 subtype F infections in IDUs vis-a-vis other populations has been discussed by researchers from São Paulo (Rossini et al, 2001;Sabino et al, 1996). However, although a high prevalence of HIV-1 subtype F has been verified among the IDU population from Rio de Janeiro, our studies did not confirm any specific segregation pattern in the IDUs so far assessed (Guimarães et al, 2001).…”
Section: Introductioncontrasting
confidence: 85%
“…Thus it is important to monitor subtype profiles, as their distribution has local determinants, and data from one site cannot be generalized for the entire country or even for a single geographic region. HIV-1 subtype B is the most prevalent in our country, followed by subtype F1, with sporadic cases of subtypes C, D, and A (Rossini et al 2001, Gadelha et al 2003, Soares et al 2003.…”
Section: Discussionmentioning
confidence: 94%
“…Previous studies analyzing samples from the city of Sao Paulo and surrounding areas have shown prevalences of 80% to 81% for subtype B, 0% to 10 for subtype C, 0% to 19% for subtype F, and 0% to 10% for B/U. 16,72 A recent study analyzing full-length HIV-1 genomes from 11 individuals with RI in Sao Paulo showed no relevant prevalence of clades other than B or recombinants (72.7% B and 18.2% B/F recombinants). 15 Monitoring the genetic diversity of HIV-1 in Brazil is central to understanding the molecular epidemiology and the spread of the epidemic.…”
Section: Discussionmentioning
confidence: 99%